Mathematics Communication Skill Seen from Self-Efficacy of Junior High School Students on 7E Learning Cycle with Ethnomathematics Nuances (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe mathematics communication skill seen from self-efficacy on high, moderate, and low categories. It was done for VII graders of Public Junior High School 1 Takengon in academic year 2018/2019. This mixed method research used sequential explanatory strategy. It is a procedure to collect quantitative and qualitative data orderly. The findings showed that the model was effective to improve mathematics communication skill of the students. mathematics communication skill and self-efficacy of each category has different mastery indicators. The differences occurred because students had different developments. Therefore, learning should be undertaken based on their capabilities to understand and needed self-regulation of the students which should be supported by environment.